Peripheral nervous system defects in erbB2 mutants following genetic rescue of heart development - Woldeyesus, Masresha T.; Britsch, Stefan; Riethmacher, Dieter; Xu, Lan; Sonnenberg-Riethmacher, Eva; Abou-Rebyeh, Faikah; Harvey, Richard; Caroni, Pico; Birchmeier, Carmen (Cold Spring Harbor Laboratory Press, 1999)
The ErbB2 tyrosine kinase functions as coreceptor for the neuregulin receptors ErbB3 and ErbB4 and can participate in signaling of EGF receptor (ErbB1), interleukin receptor gp130, and G-protein coupled receptors. ErbB2−/− mice die at midgestation because of heart malformation. Here, we report a genetic rescue of their heart development by myocardial expression of erbB2 cDNA that allows survival of the mutants to birth. In rescued erbB2 mutants, Schwann cells are lacking. Motoneurons form and can project to muscle, but nerves are poorly fasciculated and disorganized. Neuromuscular junctions form, as reflected in clustering of AChR and postsynaptic expression of the genes encoding the a-AChR, AChE, e-AChR, and the RI subunit of the cAMP protein kinase. However, a severe loss of motoneurons on cervical and lumbar, but not on thoracic levels occurs. Our results define the roles of Schwann cells during motoneuron and synapse development, and reveal different survival requirements for distinct motoneuron populations
Keywords: Motoneuron loss; neuromuscular synapse; coreceptor; neuregulin; AChR